THE IMPLEMENTATION OF TEACHING ENGLISH SPEAKING SKILL FOR AUTISTIC STUDENT IN SD MUHAMMADIYAH 4 BATU (A CASE STUDY OF AN AUTISTIC STUDENT) - SARI, ARIE TRIA ANGGA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Autistic Children, Learning difficulties, Teaching Speaking.Almost all children with autism have abnormality and or developmental disorders appear before the age of three years with type characteristics not normally in three areas:  social interaction, communication, and behavior repeated as defined. The impairments which exist in autistic children will affect their learning process also. Therefore becoming aware of learning difficulties faced by autistic children and getting the necessary help early can become the key to an autistic child’s future. The researcher focuses on kind of learning difficulties faced by autistic children in case of learning English in speaking skill, kind of teaching difficulties faced by teacher in case of teaching English speaking skill for autistic children, and also focuses on kind of teaching strategies which are used by SD Muhammadiyah 4 to overcome the learning difficulties faced by autistic children. This study used qualitative approach. The subject being investigated was an autistic child on the third grade at SD Muhammadiyah 4. The data were obtained from observation in IIIB class and in the participant’s house. In answering the second and the third of problem of the study, the researcher also interviewed the teacher and the parents of the student. The result reveals that there are learning difficulties faced by autistic children such as having poor concentration, difficulties in memorizing vocabulary, having a low confidence, having less eye contact, having inability to make a good interaction with others, difficulties in understanding complex sentence, and difficulties in communication. Meanwhile, teaching difficulties such as the difficulty in making communication with the autistic child, difficulty in teaching vocabulary, and difficulty to make student focus on the lesson. The teaching media used by the teacher some visual aids, video, and English song. The teaching strategies include drilling, Donkey Bridge, speech therapy, interviews activity, and describing picture.The researcher suggests the school to add the number of teacher in class in order to maximize the teaching process. For the teacher, they should read more references deals with autistic children. For the parents, they should keep updates to their child’s condition and give them a routine therapy. For further researcher, they can investigate the teaching strategies used in teaching other English skills such as writing, reading, and listening for autistic children.